The fundamental absorption edge and optical constants of some charge transfer compounds - Yakuphanoğlu, Fahrettin; Arslan, M (Elsevier, 2004)
A series of the charge-transfer compounds determined as 1:1 stochiometric ratio by job method has been prepared with the interaction of 7,7,8,8-tetracyanoquinodimethane (TCNQ) and anthracene, 9-methylanthracene, 9-bromanthracene in dichloromethane at room temperature. The values of the optical band gap E-g, and Urbach energy E-0 were determined from the optical absorption. The optical absorption measurements indicate that the absorption mechanism is due to allowed direct transitions for the compounds and it is evaluated that the optical band gap and Urbach energy values changes with incorporating R group in the compounds. The optical constants such as refractive index n, and extinction coefficient k and real and imaginary part of dielectric constant and optical conductivity of the compounds were calculated. E-g and E-0 reflect the influence of different types of disorder on the absorption spectra processes. Thus, a correlation between E-g and E-0 was made. Form this correlation, G value that is proportional to the second-order deformation potential and, E-f value that depend on local coordination, parameters are found to be 0.29 and 2.37 eV, respectively. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: charge-transfer compound; optical constants; optical band gap